Interstellar hydrocarbons: degradation chemistry in diffuse clouds. Issue 3 (3rd February 2022) - Awad, Zainab; Viti, Serena
ABSTRACT: Observations of diffuse clouds showed that they contain a number of simple hydrocarbons [e.g. CH, C2 H, (l- and c-)C3 H2, and C4 H] in abundances that may be difficult to understand on the basis of conventional gas-phase chemical models. Recent experimental results revealed that the photodecomposition mechanisms of hydrogenated amorphous carbon (HAC) and solid hexane release a range of hydrocarbons into the gas, containing up to six C-atoms for the case of HAC decomposition. These findings motivated us to introduce a new potential input to interstellar chemistry: the 'top-down' or degradation scheme, as opposed to the conventional 'build-up' or synthesis scheme. In this work, we demonstrate the feasibility of the top-down approach in diffuse clouds using gas–grain chemical models. In order to examine this scheme, we derived an expression to account for the formation of hydrocarbons when HACs are photodecomposed after their injection from grain mantles. Then, we calculated the actual formation rate of these species by knowing their injected fraction (from experimental work) and the average rate of mantle carbon injection into the interstellar medium (from observations). Our preliminary results are promising and reveal that the degradation scheme can be considered as an efficient mechanism for the formation of some simple hydrocarbons in diffuse clouds. However, an actual proof of the efficiency of this process and its rate constants would require comprehensive experimental determination.